A critical commentary on follow-up studies and "desistance" theories about transgender and gender-nonconforming children. Issue 2 (3rd April 2018) - Temple Newhook, Julia; Pyne, Jake; Winters, Kelley; Feder, Stephen; Holmes, Cindy; Tosh, Jemma; Sinnott, Mari-Lynne; Jamieson, Ally; Pickett, Sarah
ABSTRACT: Background : It has been widely suggested that over 80% of transgender children will come to identify as cisgender (i.e., desist ) as they mature, with the assumption that for this 80%, the trans identity was a temporary "phase." This statistic is used as the scientific rationale for discouraging social transition for pre-pubertal children. This article is a critical commentary on the limitations of this research and a caution against using these studies to develop care recommendations for gender-nonconforming children. Methods : A critical review methodology is employed to systematically interpret four frequently-cited studies that sought to document identity outcomes for gender-nonconforming children (often referred to as "desistance" research). Results : Methodological, theoretical, ethical, and interpretive concerns regarding four "desistance" studies are presented. The authors clarify the historical and clinical contexts within which these studies were conducted to deconstruct assumptions in interpretations of the results. The discussion makes distinctions between the specific evidence provided by these studies versus the assumptions that have shaped recommendations for care. The affirmative model is presented as a way to move away from the question of, "How should children's gender identities develop over time?" toward a more useful question: "How should children best be supported as their gender identity develops?" Conclusion : The tethering of childhood gender diversity to the framework of "desistance" or "persistence" has stifled advancements in our understanding of children's gender in all its complexity. These follow-up studies fall short in helping us understand what children need. As work begins on the 8th version of the Standards of Care by the World Professional Association for Transgender Health, we call for a more inclusive conceptual framework that takes children's voices seriously. Listening to children's experiences will enable a more comprehensive understanding of the needs of gender-nonconforming children and provide guidance to scientific and lay communities.